Damage Prognosis: For Aerospace, Civil and Mechanical Systems - Inman, Daniel J.; Farrar, Charles R.; Lopes, Vicente [UNESP]; Steffen, Valder (My University, 2005)
Damage prognosis is a natural extension of damage detection and structural health monitoring and is forming a growing part of many businesses. This comprehensive volume presents a series of fundamental topics that define the new area of damage prognosis. Bringing together essential information in each of the basic technologies necessary to perform damage prognosis, it also reflects the highly interdisciplinary nature of the industry through the extensive referencing of each of the component disciplines. Taken from lectures given at the Pan American Advanced Studies Institute in Damage Prognosis sponsored by the US National Science Foundation in cooperation with Los Alamos National Laboratories, this book will be essential reading for anyone looking to get to grips with the fundamentals of damage prognosis. Presents the 'ground rules' for Damage Prognosis. Deals with interdisciplinary topics: rotating machines, aerospace structures, automotive components and civil structures. Covers essential technical material: equations, graphs and plots, tables and photographs. Offers additional material from the associated workshop on an active web site. © 2005 John Wiley & Sons, Ltd.